Online Sale of Pirated Books from a Legal and Moral Perspective - Kartika Wati, Ratna; Usman, Zuraini Jamil; Soediro, Soediro (Faculty of Law, Universitas Jenderal Soedirman, 2024)
The increase in online book sales without permission and copyright violations in Indonesia poses a major threat to written works. This problem requires normative legal and moral studies to find solutions that complement previous research. This article aims to analyze and describe the legal regulations for buying and selling pirated books online and explain that the act of pirating books for sale is a moral crime. Normative legal research was used, which produced prescriptive conclusions. The data in this article consists of the Copyright Law, Information and Electronic Transactions Law, and other technical regulations. These regulations are equipped with various supporting references that discuss copyright issues, moral rights, and integrative legal theory, which describes a comprehensive legal system for responding to regulatory violations. This article reveals that national legal policies are not sufficient to guarantee protection for authors and publishers against book piracy and even make it difficult to report this crime to the police so that the use of the criminal justice system becomes ineffective. Indonesian society's perception of book piracy must be improved from previously being a common practice to a moral crime that is financially detrimental, and to the good name of authors and publishers. This article suggests several changes to the regulatory structure. First, we determine the authenticity verification scheme for books sold in bookstores and on marketplace platforms. Second, eliminating the concept of Klach Delict in criminal provisions so that reporting the crime of book piracy can be done by anyone, especially publishers and the public, who observe copyright.